Trees For Food Security-2 Project, Overview and Achievements - Muthuri, Catherine W.; Kinuthia, R.; Kuria, A.; Njoki, C. (World Agroforestry Centre, 2021)
The ‘Trees for Food Security phase 2 (T4FS-2) project stemmed from the successful completion of phase one’s four-year term project. Learnings obtained from the first phase showed that for enhanced food security and improved livelihoods, establishment of a greater diversity of trees on farms was essential. During the first phase, project stakeholders testified on the benefits obtained from the project. They also emphasized the need for project to reach more farmers in different sites or contexts. It is against this back drop that the second phase of the project was conceived with the aim of improving food security and smallholder livelihoods through the widespread adoption of appropriate locally adapted agroforestry practices in key agricultural landscapes in Ethiopia, Rwanda and Uganda.